EFFECT OF WORKING CAPITAL AND PRODUCTION ABILITY TO FINANCIAL PERFORMANCE OF UMKM - Rajindra, Rajindra; Burhanuddin, Burhanuddin; Wahba, Wahba; Guasmin, Guasmin; Febrianti, Dasa (Jurnal Sinar Manajemen, 2018)
The UMKM policies that developed during the reform era indicated that the political communication process itself has not gone well. This study aims to determine the Effect of Working Capital and Production Capability to Financial Performance of UMKM. This research uses explanatory or confirmatory research. This research was conducted in Donggala Regency 2012. The population of this study as many as 1752 scattered throughout the District within the district of Donggala. The sample in this research is 326. Data analysis used Path Analysis (Path Analysis). The results of this study indicate that there is significant influence between Working Capital and Production Capability to Financial Performance of UMKM. Suggestions from this study for funding policy for UMKM actors should consider the use of retained earnings in addition to meeting working capital requirements, operational costs, purchase of production equipment, should also be directed to anticipate unexpected costs.Â